Shakespeare's language in digital media : old words, new tools - Jenstad, Janelle; Kaethler, Mark; Roberts-Smith, Jennifer (Abingdon ; New York, N.Y. : Routledge, 2018)
"The authors of this book ask how digital research tools are changing the ways in which practising editors historicize Shakespeare's language. Scholars now encounter, interpret, and disseminate Shakespeare's language through an increasing variety of digital resources, including online editions such as the Internet Shakespeare Editions, searchable lexical corpora such as the Early English Books Online-Text Creation Partnership or the Lexicons of Early Modern English collections, high-quality digital facsimiles such as the Folger Shakespeare Library's Digital Image Collection, text visualization tools such as Voyant, apps for reading and editing on mobile devices, and more. What new insights do these tools offer about the ways Shakespeare's words made meaning in their own time? What kinds of historical or historicizing arguments can digital editions make about Shakespeare's language? A growing body of work in the digital humanities allows textual critics to explore new approaches to editing in digital environments, and enables language historians to ask and answer new questions about Shakespeare's words. The authors in this unique book explicitly bring together the two fields of textual criticism and language history in an exploration of the ways in which new tools are expanding our understanding of Early Modern English" --
Introduction (Jennifer Roberts-Smith and Janelle Jenstad) Part One: Old Words through New Tools: Re-reading with LEME and EEBO-TCP 1. Beyond the OED Loop: Digital Resources and the Arden 3 Cymbeline (Valerie Wayne) 2. Shakespeare's Hard Words and Our Hard Senses (Ian Lancashire) 4. Early Modern Terms of Art: Using Contemporary Lexicons to Read Shakespeare's Law and Botany (Daniel Aureliano Newman) 5. Hamlet's Soliloquys: A Case Study for the Expansion of the Mother Tongue (Elizabeth Bernath) Part Two: New Ways with Old Words: Curating Language 6. Storing and Accessing Knowledge: Digital Tools for the Study of Early Modern Drama (Laura Estill) 7. Words Meet Worlds: Multi-Media Digital Contextualization in the Classroom (Emily Sherwood) 8. Curating Scholarly Commentary in the Age of Google (Sarah Neville) Part Three: New Ways with New Tools: Performing Historicity 9. Database-oriented Annotation of Early Modern Plays (Jesaus Tronch) 10. Interdisciplinarity, Multidisciplinarity, and the Digital Queen's Men Editions (Andrew Griffin) 11. Digital Parallel-text Approaches to Performance Historiography (Toby Malone, University of Waterloo) 12. Marginalia: A Textual Revolution Without Casualties (Eric Johnson).
Keywords: Shakespeare, William, -- 1564-1616 -- Criticism and interpretation -- Data processing; Shakespeare, William, -- 1564-1616 -- Criticism, Textual; Shakespeare, William, -- 1564-1616 -- Language; English language -- Early modern, 1500-1700 -- Data processing; English language -- History -- Data processing